Recent Tectonic Deformation of the Lunar Farside Mare and South Pole–Aitken Basin - C. A. Nypaver; T. R. Watters; J. D. Clark (The Planetary Science Journal)
The timing and scale of lunar tectonism provide a crucial insight into the geologic evolution of Earth’s Moon. Within the nearside lunar maria, wrinkle ridges formed during and after the emplacement of the mare basalts as a result of subsidence-induced contraction. Past analyses of lunar wrinkle ridges and associated fault structures have helped to constrain lunar tectonic and thermal history. However, contractional tectonics in the lunar maria may not be limited to the formation of large-scale structures in the distant geologic past. In contrast to larger, subsidence-induced lunar wrinkle ridges, recent investigations have identified contractional structures within the nearside lunar maria that are dimensionally small and recently formed via a combination of global stresses. The identification of those small mare ridges (SMRs) demonstrated that the lunar nearside maria are subject to compressional stresses that are recently and potentially currently active, but the presence of such features in the lunar farside maria was never investigated. Furthermore, the exact timing of SMR formation and the geometry of the associated fault structures remain poorly constrained. Here, we present the first observations of widespread SMRs in the lunar farside maria and South Pole–Aitken Basin. We also derive absolute model age estimates for SMR formation, and we constrain SMR-forming fault geometries via elastic dislocation modeling. Our analysis provides the first globally complete perspective of recent lunar tectonics, and we show that lunar fault structures may be recently and potentially currently active within regions of interest for upcoming lunar missions.